2006
DOI: 10.1182/blood-2005-09-3687
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein VI–dependent and –independent pathways of thrombus formation in vivo

Abstract: The role of the collagen receptor glycoprotein VI (GPVI) in arteriolar thrombus formation was studied in FcR␥-null mice (FcR␥ ؊/؊ ) lacking platelet surface GPVI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
246
4
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 204 publications
(269 citation statements)
references
References 30 publications
15
246
4
4
Order By: Relevance
“…The mice also display resistance to thrombosis in two distinct vascular injury models, one in a mediumsized artery (the carotid) exposed externally to FeCl 3 and the other in a cremaster muscle arteriole exposed from within to light-excited Rose Bengal. The thrombotic response to injuries caused by FeCl 3 has been shown to be collagen-dependent (33). In lymphocytes, sema4D on T cells promotes B cell receptor signaling by binding to CD72.…”
Section: Discussionmentioning
confidence: 99%
“…The mice also display resistance to thrombosis in two distinct vascular injury models, one in a mediumsized artery (the carotid) exposed externally to FeCl 3 and the other in a cremaster muscle arteriole exposed from within to light-excited Rose Bengal. The thrombotic response to injuries caused by FeCl 3 has been shown to be collagen-dependent (33). In lymphocytes, sema4D on T cells promotes B cell receptor signaling by binding to CD72.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that thrombin is the major platelet agonist involved in thrombus formation following laser-induced injury under our conditions (35). To exclude the possibility that thrombin generation was defective in BSDL-null mice in comparison with wild-type mice, fibrin accumulation at the site of injury was compared in BSDL-null and wild-type mice.…”
Section: Conditionsmentioning
confidence: 99%
“…This system was appropriate for our purposes because the consequences of FeCl 3 treatment of mouse mesentery are known. First, FeCl 3 treatment causes denudation of the arterial endothelium and the coincident exposure of what appears to be VWF 44 and collagen 45 of the subendothelium, thereby generating a thrombogenic surface. Second, VWF is the dominant molecule involved in platelet deposition on the damaged endothelium of FeCl 3 -treated vessels.…”
Section: Gpib-dependent Fecl 3 -Induced Stable Occlusion Of the Carotmentioning
confidence: 99%